2015
DOI: 10.4236/aid.2015.54017
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Scrub Typhus: A Prospective Analysis of Clinical and Epidemiological Profile of Patients from a Tertiary Care Hospital in New Delhi

Abstract: Introduction: Scrub typhus is a febrile illness caused by Orientia tsutsugamushi which is transmitted by the larval stage of trombiculid mites. It has varied manifestations ranging from mild disease to fatal illness. The classical manifestations include fever, rash, lymphadenopathy and eschar. Serology is the preferred diagnostic tool with indirect immunofluorescence assay (IFA) as the current gold standard. Material & Methods: A total of 229 clinically suspected cases of Scrub typhus from 15 th of October 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…8,9 This seasonal pattern should alert the treating physicians to consider scrub typhus in the list of differentials that commonly includes only dengue and malaria during these months. 10 An outbreak investigation of FUO in 2003 was investigated in Shimla, HP (Indira Gandhi Medical College) and scrub typhus was confirmed through lab diagnosis in most of the districts of the state. 11 An analysis from a tertiary centre in Rajasthan showed that both dengue and malaria follow the same seasonal pattern in both years with increased incidence of scrub typhus (24% in 2012 to 35.23% in 2013) and dengue (47% in 2012 to 56% in 2013).…”
Section: Resultsmentioning
confidence: 99%
“…8,9 This seasonal pattern should alert the treating physicians to consider scrub typhus in the list of differentials that commonly includes only dengue and malaria during these months. 10 An outbreak investigation of FUO in 2003 was investigated in Shimla, HP (Indira Gandhi Medical College) and scrub typhus was confirmed through lab diagnosis in most of the districts of the state. 11 An analysis from a tertiary centre in Rajasthan showed that both dengue and malaria follow the same seasonal pattern in both years with increased incidence of scrub typhus (24% in 2012 to 35.23% in 2013) and dengue (47% in 2012 to 56% in 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier scrub typhus was considered to occur mostly in rural areas; however, now India as a whole has been shown to be endemic for it with outbreaks reported even from the metropolitans [5][6][7][8]. A retrospective study on 709 patients admitted at a tertiary care hospital in South India has identified farming, not wearing shirt at home, living in houses adjacent to bushes and shrubs as risk factors for acquiring the infection [12].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence is confined to the 'tsutsugamushi triangle' (Japan and eastern Russia in north, northern Australia in south to Afghanistan in west) and it has traditionally been considered to be a disease of rural areas affecting people engaged in farming [1]. Lately, there have been many outbreaks in India reported from the states of Himachal Pradesh, Uttarakhand, Rajasthan, New Delhi, Chandigarh, Goa, Andhra Pradesh and Meghalaya [2][3][4][5][6][7][8][9]. Some of these regions were oblivious to the disease until recent times.…”
mentioning
confidence: 99%
“…Scrub typhus, like most other tropical infections, is found most often during the postmonsoon season. 1,2 Patients with scrub typhus present with fever in addition to a variety of nonspecific symptoms and findings. These often manifest within 10 days of being bitten by a mite.…”
Section: Discussionmentioning
confidence: 99%